Long non-coding RNA CCAT1/miR-218/ZFX axis modulates the progression of laryngeal squamous cell cancer - Yaming Zhang; Haili Hu (Tumor Biology, 2017)
Long non-coding RNAs have been proved to be closely associated with different cancers. This study was designed to elucidate the function and mechanisms of colon cancer–associated transcript-1 in the progression of human laryngeal squamous cell cancer. Expressions of colon cancer–associated transcript-1, microRNA-218, and zinc finger protein, X-linked messenger RNA were measured using quantitative real-time polymerase chain reaction, and the expression level of zinc finger protein, X-linked protein was detected using western blot. Proliferation and invasion of laryngeal squamous cell cancer cell lines were detected by Cell Counting Kit-8 assay and Transwell invasion assay, respectively. Luciferase assay was used to confirm whether microRNA-218 is a target of colon cancer–associated transcript-1 and whether microRNA-218 directly binds to 3′-untranslated region of zinc finger protein, X-linked messenger RNA. Effect of colon cancer–associated transcript-1 on tumor growth was observed through xenograft mice models in vivo. The results showed that expressions of colon cancer–associated transcript-1 and zinc finger protein, X-linked were significantly higher while microRNA-218 expression was significantly lower in the laryngeal squamous cell cancer tissues than those in the adjacent normal tissues. MicroRNA-218 overexpression or zinc finger protein, X-linked silencing significantly suppressed proliferation and invasion of laryngeal squamous cell cancer cells. Moreover, knockdown of colon cancer–associated transcript-1 significantly inhibited proliferation and invasion of laryngeal squamous cell cancer cells, which were reversed by microRNA-218 downregulation or zinc finger protein, X-linked upregulation. Finally, colon cancer–associated transcript-1 silencing inhibited xenograft tumor growth of laryngeal squamous cell cancer in vivo. In conclusion, colon cancer–associated transcript-1 knockdown inhibits proliferation and invasion of laryngeal squamous cell cancer cells through enhancing zinc finger protein, X-linked by sponging microRNA-218, elucidating a novel colon cancer–associated transcript-1–microRNA-218–zinc finger protein, X-linked regulatory axis in laryngeal squamous cell cancer and providing a promising therapeutic target for laryngeal squamous cell cancer patients.